Antimicrobial Activity of Kedawung Extract (Parkia Roxburghii G. Don) on Food Borne Pathogens - Ervizal A. M Zuhud; Winiati Pudji Rahayu; C. Hanny Wijaya; Pipi Puspita Sari (Jurnal Teknologi dan Industri Pangan, 2001)
Kedawung is a Leguminosae/Fabaceae which. It is commonly used as traditional medicine for infection and stomach disoders, caused by bacteria. The aim of this study is to examine the potential antimicrobial activity of seed, bark, root and kedawung leaf. It is expected that the result will give information on characteristics and concentration of kedawung part which have the highest antimicrobial activity. The result showed that the bark has the highest antimicrobial activity on Escherichia coli, Vibrio cholerae, Staphylococcus aureus and Bacillus cereus. Extract made from kedawung plant and water (ratio 1:2,b/v) was better than those made with ratios of 1 : 1 or 1 : 3 (b/v). Heat did not decrease its antimicrobial activity. Extract concentration of 10% (21.40 mg/ml) with contact time of 24 hour decreased bacterial growth but did not inactivate them.